(untitled) (Research, Society and Development, 2020)
Analyzing the different aspects related to the mental health and risk factors for elderly suicide and verify its association with COVID-19 pandemic. This is an integrative literature review carried out by a search for scientific articles indexed in electronic databases available on Virtual Health Library (VHL) and SciELO. The keywords used were: “mental health” OR “suicide” AND “elderly” OR “aged” AND “pandemics” AND “covid-19” OR “coronavirus”, and included 33 articles. The most associated factors with the suicide of brazilian elders were: health problems, isolation, violence, financial problems and loss of loved ones. Brazilian studies that addressed biopsychosocial aspects of suicide used, mostly, semi-structured interviews as methodological path. Studies that address the mental health of the elderly in the midst of the pandemic have European, North American and Asian origins, with varied methodologies. These showed that covid-19 isolation comprises risk factors for suicide among the elderly. Although some studies point to the resilience of the elderly during the pandemic, the research in general has explained the vulnerability to the risks to mental health. Therefore, the COVID-19 pandemic can bring consequences to the health of the population, reflecting also on mental health – due to the multiplicity of associated losses, especially among the elderly. Regarding the pre-pandemic studies, it was noted that the confinement for covid-19 presents challenges and risk factors for suicide among this population. In Brazil, public policies aimed at preventing suicide among the elderly are still not a priority, making it difficult to identify risk factors for suicidal ideations.